2020
DOI: 10.2147/dddt.s282932
|View full text |Cite
|
Sign up to set email alerts
|

<p>Punicalagin Inhibits Tert-Butyl Hydroperoxide-Induced Apoptosis and Extracellular Matrix Degradation in Chondrocytes by Activating Autophagy and Ameliorates Murine Osteoarthritis</p>

Abstract: Background Osteoarthritis (OA) is a prevalent articular disorder and has no entirely satisfactory treatment. Punicalagin (PUG) is a polyphenol which has shown multiple pharmacological effects on various diseases. However, the role of PUG in the treatment of OA has not been well defined. Methods The effects of PUG on anti-oxidative stress, anti-apoptosis, extracellular matrix (ECM) degradation and autophagy were evaluated in chondrocytes through Western blot and immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
(60 reference statements)
1
21
0
Order By: Relevance
“…In five articles, both animal and in vitro designs were detected. 24 , 25 , 27 , 28 , 47 Tables 2 - 4 demonstrated details of investigations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In five articles, both animal and in vitro designs were detected. 24 , 25 , 27 , 28 , 47 Tables 2 - 4 demonstrated details of investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, animal and in vitro studies showed benefits of pomegranate in improving clinical features and reducing inflammatory and oxidative markers in OA. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]47 Discrepancy in findings on the clinical status and inflammatory markers between studies can be due to using different dosages, administration types, and preparation procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al found that PUG promotes autophagy through the forkhead box O1/proteoglycan 4 (FOXO1/Prg4)/HIF3 α axis, inhibits inflammation and extracellular matrix degradation, and attenuates inflammatory damage caused by lipopolysaccharide (LPS) in rat chondrocytes ( Liu et al, 2021 ). In addition, Kong injected PUG in a mouse DMM model and showed that PUG increased antioxidant enzymes and reduced the degradation of apoptotic proteins and ECM by mediating autophagy, thus effectively stopping the progression ( Kong et al, 2020 ). Although preclinical studies have shown that PUG can reduces chondrocyte apoptosis and ECM degradation through mediating autophagy, its solubility is low and insufficient for effective use after oral administration, which greatly limits its clinical application ( Cerdá et al, 2005 ).…”
Section: Phytochemicals For the Treatment Of Oa By Promoting Autophagymentioning
confidence: 99%
“…Previous studies aver that osteoarthritis (OA) is the most common degenerative joint disease [1], which is characterized by degradation of extracellular matrix (ECM) or progressive loss of cartilage [2,3]. With rising number of elderly population, number of patients with osteoarthritis is increasing, which adversely affect quality of life of elderly patients.…”
Section: Introductionmentioning
confidence: 99%